PENGARUH CAMPURAN PUPUK ORGANIK DAN MULSA ORGANIK TERHADAP PERTUMBUHAN STEK TANAMAN BUAH NAGA (Hylocereus costaricensis) - Muhammad Pasco Nawly; Wardati Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Dragon fruit (Hylocereus costaricensis) is one of the cactus plants that are relatively new in the middle of Indonesian people and quite popular because it tastes sweet and has a variety of health benefits. One way to increase productivity is with the selection of good crop seeds. Plant multiplication has two ways that are vegetative and generative. The multiplication of plant plants used is cuttings. For the growth of goodcuttings then it is necessary planting media that has a lot of nutrient content that is with the addition of organic fertilizer (goat + cow) and mulch organic (sawdust). This research aims to get interaction of organic fertilizer composition with organic mulch and best dose for breeding dragon fruit crop cuttings. The research was conducted in the experimental plantation, Faculty of Agriculture, University of Riau from April to September 2017. The treatment given is the dosing of organic fertilizer with the following doses : P0 = whitout treatmented P1 = (10 ton. Ha-1 + 20 ton. Ha-1), P2 = (20 ton. Ha-1 + 10 ton. Ha-1), M0 = without treatmented, M1 = (5 ton. Ha-1), M2 = (8 ton. Ha-1). The research was conducted experimentally using a complete randomized design method (RAL) both combined factors, gained 9 combinations of treatment and each treatment repeated 3 times, so there were 27 units of experiments. Based on the results of the study of organic fertilizer goat and cow with a composition of organic fertilizer mixture(goat 20 ton. Ha-1 + cows 10 ton. Ha-1) and organic mulch 5 ton. Ha-1 is the best treatment in increasing the growth of fruit crop cuttings dragon fruit. Keywords: dragon fruit cutting,organic fertilizer, organic mulch.